Two dominant boreal conifers use contrasting mechanisms to reactivate photosynthesis in the spring - Qi Yang (Nature Portfolio, 2020)
Boreal conifers regulate photosynthesis to maximize seasonal growth while limiting damage due to light and cold stress. Here Yang et al. show that two major conifer species achieve this via different means as Scots pine, but not Norway spruce, activates alternative electron sinks during spring.